2019
DOI: 10.1080/01629778.2019.1568268
|View full text |Cite
|
Sign up to set email alerts
|

Economic inequality in satisfaction with healthcare in the Baltic countries during and after the economic crisis (2008–2014)

Abstract: Public satisfaction with healthcare systems is an important dimension of healthcare legitimacy. The paper analyzes how satisfaction with healthcare systems depended upon the economic situation of our respondents during and after the economic recession in the Baltic states. The results show that there were no differences in public satisfaction with healthcare between better and worse off people in Estonia (except in 2009). In Lithuania, however, satisfaction among the economically better off was higher compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…While evidence on the relationship between income and satisfaction in ‘normal’ times is inconclusive, a few recent studies demonstrate that one’s income can be a good predictor of his or her healthcare satisfaction in the crisis context (AlSaud et al, 2018; Popic et al, 2018; Roots et al, 2019). A country study of healthcare satisfaction in crisis-hit Portugal finds that satisfaction of individuals with lower income dropped particularly strongly compared to satisfaction of those with higher income, whose satisfaction levels show minor and insignificant changes (Popic et al, 2018).…”
Section: Individual Determinants Of Healthcare Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…While evidence on the relationship between income and satisfaction in ‘normal’ times is inconclusive, a few recent studies demonstrate that one’s income can be a good predictor of his or her healthcare satisfaction in the crisis context (AlSaud et al, 2018; Popic et al, 2018; Roots et al, 2019). A country study of healthcare satisfaction in crisis-hit Portugal finds that satisfaction of individuals with lower income dropped particularly strongly compared to satisfaction of those with higher income, whose satisfaction levels show minor and insignificant changes (Popic et al, 2018).…”
Section: Individual Determinants Of Healthcare Satisfactionmentioning
confidence: 99%
“…A country study of healthcare satisfaction in crisis-hit Portugal finds that satisfaction of individuals with lower income dropped particularly strongly compared to satisfaction of those with higher income, whose satisfaction levels show minor and insignificant changes (Popic et al, 2018). Another study, on all Baltic countries, found that individuals’ economic situation, as measured through difficulties in paying bills, was related to healthcare satisfaction, such that those who more often experienced these difficulties were less satisfied (Roots et al, 2019). The analysis in question also revealed country variation in the association between the economic differences and satisfaction, with this association being the strongest in Latvia, the country whose healthcare system was hit the hardest by the crisis.…”
Section: Individual Determinants Of Healthcare Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estonia and Lithuania have social health insurance systems underpinned by employment-based contributions with government funding for other non-employed groups, while in Latvia there is a national healthcare system funded through income tax and general revenues 9 , 10 . Although these systems provide extensive medical coverage (from over 90% of the population in Estonia and Lithuania to universal coverage in Latvia), high user charges (in Latvia) and substantial out-of-pocket payments can limit access to healthcare services, especially in disadvantaged groups 9 , 11 . Comparatively little is known about the epidemiology of epilepsy in the Baltic countries 12 .…”
Section: Introductionmentioning
confidence: 99%